The Selection of Spouse With Free and Full Consent, A Comparison between Islam and UDHR Article 16 (A Comparative Study) - Mehmood, Asad; Saeed, Abid (Al-Irfan, 2023)
An Essential motive to choose this topic is that to share Islamic version about selection of spouse for marriage as compare to Universal Declaration of Human Rights (UDHR) Article 16 which also considered about selection of spouse. UDHR and Islam deliberated about significance of Marriage for both man and women to extend their family but have some difference of standard about Selection of spouse for Marriage .In this article we will share point of UDHR article 16 and Islamic vision about Selection of spouse for marriage .This article will also explain comparison between Islamic and United Nation Human right charter explanation about Selection of spouse with free and full consent. Islam allow boy or girl to choose their life partner will free and full consent under Islamic law but with the advice and guideline of parents or elder ,while UDHR authorized boy and girl to may choose their spouse with full authority without any limitation of race, color ,religion or nationality. Although all Muslim countries signed this United Nation Human right charter so after signing this charted they need to follow UN Human right charter all 30 articles but now they realize that this charter have difference criteria about selection of spouse which causing clash, same time United Nation Human Right Department considering around 1.8 Billion Muslim Population as major part of the world population ,second largest Religion of the world that Muslim can practice their religious beliefs freely with considering of International Human Right charter .This article will assist Muslim population to recognize, reconsideration and attempt to modification some articles of Universal Declaration of Human Rights (UDHR) especially regarding Spouse selection criteria for Marriage (Nikah), and UN Human right department need to re-consider this point under different religions and regional beliefs ,regional and culture value.